The Cambridge–Cambridge controversy on the theory of capital: 50 years after - Harald Hagemann (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
The paper points out that capital theory has always been a hotly debated subject, partly because the theoretical issues involved are very complex, and partly because rival ideologies and value systems directly affect the issues discussed. The focus is on the history, the main protagonists, and the relevant problems examined and argued about during the two Cambridges controversy on the theory of capital which was at its peak 50 years ago. Whereas one clear result of these debates is that neither Samuelson's surrogate production function nor Solow's rate-of-return concept could resurrect aggregate neoclassical theory, many other questions, such as the treatment of capital in temporary or intertemporal general equilibrium models or the empirical relevance of the reswitching phenomenon, are still discussed controversially.
Keywords: B25; B51; C67; D57; E22; O33; 330; Austrian theory of capital; capital theory; Cambridge controversy; reswitching; Sraffa; wage-profit curve; Wicksell effects